Instituição militar e política, uma abordagem antropológica (1964-1974) - Frederici, Sandra Maria (2003)
The purpose of this dissertation is thinking the relationship between the military institution and politics in the period between 1964-1974, by an anthropological reading of the processes occurred in the core of the military hierarchy. Therefore, its analysis deals with the military careers constructed in this period, as well as the intramilitary political arrangements, as fields able to better evidence the movements in the command sequence under the new position assumed in the political context. In this way, based on an approach that considers the army as a specific social organization, that discussion aims to treat its relation with politics through its internal articulations, all of them concerning, as a last resort, to the central dimension of the military universe: the hierarchal organization.